Financial Performance Analysis of Property and Real Estate Companies Listed on The Indonesia Stock Exchange With Du Pont System Approach - Mursalin Mursalin; Nurkardina Novalia; Anisa Layanti (International Journal of Social Science, Education, Communication and Economics (SINOMICS JOURNAL), 2023)
This study aims to determine the financial performance of property and real estate companies in the LQ45 index for the 2017-2021 period listed on the Indonesia Stock Exchange using the Du Pont System approach. Du Pont System is an analysis that unites activity ratios with profitability constellations to show how these two factors relate in determining return on investment, namely the profitability of company assets. This research is analyzed using qualitative descriptive analysis techniques by analyzing financial statements using the Du Pont System approach that has been published on the Indonesia Stock Exchange which describes real circumstances or events in the company. The data collection techniques used in this study are documentation techniques and literature studies. The results showed that the financial performance of PT Pakuwon Jati Tbk had the highest ROI of 8.38% while PT PP Properti Tbk with the lowest ROI rate of 4.37%, PT Pakuwon Jati Tbk became the company with the best corporate financial performance when compared to other property and real estate companies for the 2017-2021 period.